2005
DOI: 10.4049/jimmunol.174.11.6571
|View full text |Cite
|
Sign up to set email alerts
|

The Many Faces of IL-7: From Lymphopoiesis to Peripheral T Cell Maintenance

Abstract: IL-7 is well known as a lymphopoietic cytokine, but recent studies have also identified a critical role for IL-7 in peripheral T cell homeostasis. IL-7 is well poised to serve as a homeostatic cytokine because it is produced by resting stromal cells, the IL-7R is present on most T cells, and IL-7 down-regulates its own receptor. These features allow IL-7 to signal large numbers of resting T cells and to be efficiently used when supplies are limiting. Consistent with this, in normal hosts, IL-7 is required for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
472
2
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 506 publications
(496 citation statements)
references
References 74 publications
17
472
2
5
Order By: Relevance
“…However, activated OT-II T cells respond in vitro only to IL-2 and IL-7, with no effect of IFN-g, arguing against direct involvement of inflammatory cytokines in bystander proliferation. IL-7, unlike other members of the g c cytokine family induced during immune responses, is constitutively produced at low levels in non-lymphoid and lymphoid organs by not yet well-characterized stromal cells [23][24][25]. Interestingly, activated OT-II cells expressed IL-7Ra and this cytokine was effective in inducing proliferation of activated OT-II cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…However, activated OT-II T cells respond in vitro only to IL-2 and IL-7, with no effect of IFN-g, arguing against direct involvement of inflammatory cytokines in bystander proliferation. IL-7, unlike other members of the g c cytokine family induced during immune responses, is constitutively produced at low levels in non-lymphoid and lymphoid organs by not yet well-characterized stromal cells [23][24][25]. Interestingly, activated OT-II cells expressed IL-7Ra and this cytokine was effective in inducing proliferation of activated OT-II cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Giving IL‐15 may have additional benefits of increasing NK cell and dendritic cell survival, whereas IL‐7 is thought to be a cytokine that is targeted more toward T cells. IL‐7 is a multifunctional cytokine of the immune system that affects both T cells and B cells and induces the proliferation of naïve and memory T cells 44. Venet et al45 showed that IL‐7 treatment of isolated lymphocytes from septic patients restored T‐cell proliferation and IFN‐γ secretion.…”
Section: Immunological Modification Therapiesmentioning
confidence: 99%
“…Notably, application of IL-7 has been reported to enhance immune reconstitution during lymphopenia. IL-7 therapy is thus a significant factor for enhancing the actual thymic throughput (Fry and Mackall 2005). Recombinant IL-7 therapy enhances the total numbers of T stem cells and restores the diversity of the T cell repertoire following cytotoxic chemotherapy in human beings (Zhang et al 2015).…”
Section: Can Ati Be Reversed Therapeutically?mentioning
confidence: 99%